THE INFLUENCE OF ONLINE TEACHING ON FACE-TO-FACE TEACHING PRACTICES - Scagnoli, Norma I.; Buki, Lydia P.; Johnson, Scott D. (Online Learning, 2009)
The integration of online technologies in educational practice is rendering new opportunities for teaching and learning. It is known that instructors who have taught fully online courses have acquired new skills and have had the opportunity to implement novel pedagogical practices in the online environment. However, it is unclear whether direct exposure to fully online teaching facilitates the integration of technology in traditional classrooms. This qualitative investigation examined the transfer of four experienced faculty members’ pedagogical practices from online to face-to-face teaching. Results of this case study show that (a) the instructors’ online teaching experience influenced their perceptions and understanding of online pedagogical strategies, and (b) the transfer of pedagogical strategies back to the classroom is a complex process influenced by the instructors’ teaching style, satisfaction with working in the online environment, and the similarity of content and context between online and face-to-face courses. These findings have the potential to inform innovations in faculty training and development and to promote further research in this area.